BEYOND AESTHETICS: A DISCOURSE ANALYSIS OF IMAGERY IN “YANG MELIMPAH DARI CUCURAN ATAP PERIBAHASA” BY MARHALIM ZAINI - Rezeki, Erni Tri; Rahayu, Sri (Journal of Pragmatics and Discourse Research, 2025)
Through a discourse-analytic lens, this study explores the function and distribution of imagery in the poetry collection Yang Melimpah DariCucuran Atap Peribahasa by Marhalim Zaini. While the original approach employs stylistics to describe six forms of imagery—visual, auditory, olfactory, gustatory, tactile, and motion—this revision interrogates how those sensory strategies encode deeper ideological, cultural, and religious messages. The poems reflect postcolonial identity, religious introspection, ecological memory, and regional cultural critique. Employing a qualitative approach that combines stylistic reading with critical discourse analysis (Fairclough, 2001), this study moves beyond mere description to reveal how poetic language acts as a social semiotic. The analysis considers how metaphors, diction, and sensory images structure poetic voice and worldview. Through selected poem excerpts, the study examines how imagery evokes aesthetic response and acts as a rhetorical device for resisting dominant narratives, articulating regional pride, or expressing existential despair. Findings indicate that while visual and auditory imagery dominate, their function extends to dramatizing cultural memory, ritualized belief, and socio-political commentary. The poetic discourse constructs an implicit critique of religious formalism, ecological erosion, and postcolonial disorientation, embedded within metaphorical and imagistic expression. The study recommends that literary studies engage more deeply with discourse-sensitive poetry readings, particularly in Southeast Asia, to uncover layered meanings and ideological positions. Implications are offered for literature education, emphasizing the need to teach poetry as an aesthetic product and a form of cultural discourse that engages readers’ critical awareness. Future research may explore intertextual comparisons across regional poetic traditions or conduct corpus-based discourse analysis on Malay poetic genres.